MAQASID SYARIAH REVIEW OF KOTA BANDA ACEH QANUN NUMBER 3 OF 2021 CONCERNING PARKING SERVICE FEES ON THE EDGE OF PUBLIC ROADS: Maqasid Syariah Review - Yudi Akbar, Muhammad; Sabil, Jabbar (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2023)
Based on Qanun Number 3 of 2021, The Kota Banda Aceh Government set new tariffs at several locations to increase local revenue. This qanun inspired the writer to examine the policy based on the maqāṣid al-syarī'ah review. This study is a normative legal research that uses maqāṣid as its approach. The author performs tarjih maslahat through four steps to test the validity of maqāṣid al-khalq. This study found that the Kota Banda Aceh Government has not improved the management of parking fees, so local revenue is not optimal. From the perspective of maqāṣid al-syarī‘ah, if optimizing parking management is not carried out first, then the rate increase is tertiary (al-maqāṣid al-taḥsīniyyāt). Based on the analysis of tarjih maslahat, the tertiary benefits should not undermine secondary benefits. In addition, the new parking rate policy has more dominant mafsadat effects than maslahat because management has not optimally prevented fraud. This study concluded that resisting damage is more important than realizing benefits. Thus, in this policy, there is a conflict between maqāṣid al-khalq and maqāṣid al-syarī'ah.